The preparation and evaluation of self-nanoemulsifying systems containing Swietenia oil and an examination of its anti-inflammatory effects - Eid AM (Dove Medical Press, 2014)
Ahmad M Eid,1 Hesham A El-Enshasy,1 Ramlan Aziz,1 Nagib A Elmarzugi1,2 1Research and Innovation Department, Institute of Bioproduct Development, Universiti Teknologi Malaysia, Johor, Malaysia; 2Department of Industrial Pharmacy, Faculty of Pharmacy, Tripoli University and Biotechnology Research Center, Libyan Authority for Research, Science and Technology (LARST), Tripoli, Libya Abstract: There is an increasing trend among pharmaceutical industries to use natural bioactive materials as medicinal agents and to use new technologies such as self-nanoemulsifying systems. The solubility and bioavailability of poorly soluble drugs can be enhanced by self-nanoemulsifying systems. Swietenia oil is frequently used because of its antimicrobial, antimutagenic, and anticancer bioactive medical properties. This study was conducted to develop self-nanoemulsifying systems for Swietenia oil that will enhance the anti-inflammatory activity of the oil. The self-emulsifying systems developed for Swietenia oil in this study were constructed using ternary phase diagrams and contained the nonionic surfactants Labrasol®, Tween 20, Capmul®, and Labrafil®. The effect of these surfactants on the formulation was examined. The mean droplet size of Swietenia oil as well as their distribution, appearance, viscosity, and spreading times were studied to find the optimum formula, which contained droplets that were less than 200 nm. The next step was to test the anti-inflammatory properties of the optimum formula using a carrageenan-induced rat paw edema test. The results from this test were compared to the oil solution. Different oil/surfactants mixtures had various emulsification properties that were related to the size of their droplets. Tween 20 is a good surfactant to use in self-emulsifying systems because it produces droplets of nano-size. Mixtures of Capmul/Labrasol at a ratio of 2:1 and Labrafil/Tween 20 at a ratio of 1:2 were able to produce self-nanoemulsifying formulations containing Swietenia oil concentrations that ranged from 20%–50%. Nanoemulsion occurred when the size of the droplets fell below 200 nm with low size distribution (<0.3) after being gently mixed with water. It was found that the hydrophilic/lipophilic balance value affected the ternary phase diagram behavior of Swietenia oil and surfactants. In addition, the anti-inflammatory properties of Swietenia oil were greater in the self-nanoemulsifying systems than in the oil solution. Keywords: Labrasol, Capmul, Tween 20, Labrafil